Thiazole-Bearing 4-Thiazolidinones as New Anticonvulsant Agents - Mariia Mishchenko; Sergiy Shtrygol; Danylo Kaminskyy; Roman Lesyk (MDPI AG, 2020)
Here, we describe the synthesis and anticonvulsant activity of thiazole-bearing hybrids based on 2-imino-4-thiazolidinone and 2,4-dioxothiazolidine-5-carboxylic acid cores. The structure of target compounds was based on the following: (i) A combination of two thiazole cores; (ii) similarity to ralitolin’s structure; (iii) the compliance with structural requirements for the new anticonvulsants. Target compounds were synthesized via known approaches based on Knoenavegel reaction, alkylation reaction, and one-pot three-component reaction. Anticonvulsant properties of compounds were evaluated in two different models—pentylenetetrazole-induced seizures and maximal electroshock seizure tests. Among the tested compounds 5Z-(3-nitrobenzylidene)-2-(thiazol-2-ylimino)-thiazolidin-4-one Ib, 2-[2,4-dioxo-5-(thiazol-2- ylcarbamoylmethyl)-thiazolidin-3-yl]-N-(2-trifluoromethylphenyl)acetamide IId and (2,4-dioxo-5- (thiazol-2-ylcarbamoylmethylene)-thiazolidin-3-yl)acetic acid ethyl ester IIj showed excellent anticonvulsant activity in both models. The directions of compounds modification based on SAR aspects were discussed. The results of the study provide a basis for further study of the anticonvulsant properties of selected thiazole-thiazolidinones.